The big expansion of rural secondary schooling during the cultural revolution and the returns to education in rural China - Zhu, Mengbing,Sicular, Terry (Department of Economics, Social Science Centre, Western University, 2022)
During the Cultural Revolution China embarked on a dramatic, albeit temporary, expansion of secondary education in rural areas that affected tens of millions of children who reached secondary school age in the late 1960s and 1970s. The conventional wisdom is that this expansion was politicized and low quality. Using instrumental variables estimation, we exploit variation in the expansion across localities and birth cohorts to estimate the impact of Cultural Revolution education on individual outcomes. Creative use of historical county-level information matched with rich household survey data from the mid-1990s allows analysis of multiple outcomes. We find a significant, positive effect of Cultural Revolution years of education on off-farm employment and wage earnings. The effect on household income is mixed and likely reflects the substitution of market purchases for own production.
10419/270414
Keywords: Graue Literatur; Education expansion; secondary education; returns to schooling; rural China; Cultural Revolution